Komunikasi Matematika Siswa SMP Berkecerdasan Logis-Matematis, Linguistik, dan Spasial dalam Memecahkan Masalah Sistem Persamaan Linear Dua Variabel - Sholikha, Rizka Ayu Amanatush; Palupi, Evangelista Lus Windyana (Program Studi S1 Matematika UNESA, 2023)
Communication is an important part of learning mathematics and needs to be mastered by students. The facts show that junior high school students written and oral mathematical communication in the matter of systems of linear equations of two variables is still lacking. Intelligence is one factor that causes it. Each student has different intelligence, including logical-mathematical, linguistic, and spatial. This indicates that students written and oral mathematical communication with intelligence is related. The purpose of this research is to describe the written and oral mathematical communication of junior high school students who have logical-mathematical, linguistic, and spatial. This research is a qualitative descriptive study. The subjects of this study were two students of VIII-G and one student of VIII-H at SMPN 3 Surabaya with different types of intelligence and equal levels of mathematical ability. The data collection method in this study was through multiple intelligence test, written math communication test, oral math communication test, and interview. The results of the written and oral mathematical communication test will be analyzed to determine the written and oral mathematical communication of each subject. The results showed that students with logical-mathematical demonstrated the process of communicating mathematical ideas in writing, namely interpreting ideas from mathematical problems, expressing everyday situations or events into mathematical models, constructing arguments, and making generalizations. Students with logical-mathematical also show the process of communicating mathematical ideas orally, namely interpreting ideas from mathematical problems, expressing everyday situations or events into mathematical models, and constructing arguments. Meanwhile, students with linguistic show the process of communicating mathematical ideas in writing, namely interpreting ideas from mathematical problems and expressing everyday situations or events into mathematical models. Linguistically students also show the process of communicating mathematical ideas orally, namely interpreting ideas from mathematical problems, expressing everyday situations or events into mathematical models, constructing arguments, and making generalizations. For students with spatial, it shows the process of communicating mathematical ideas in writing, namely expressing everyday situations or events into mathematical models. Students with spatial also show the process of communicating mathematical ideas orally, namey interpreting ideas from mathematical problems, expressing everyday situations or events into mathematical models, constructing arguments, and making generalization.